Evaluation of the Abbott BinaxNOW rapid antigen test for SARS-CoV-2 infection in children: Implications for screening in a school setting. - Neeraj Sood; Rashmi Shetgiri; Anna Rodriguez; Dianna Jimenez; Sonia Treminino; Amanda Daflos; Paul Simon (PLoS ONE)
Background Rapid antigen tests hold much promise for use in the school environment. However, the performance of these tests in non-clinical settings and among one of the main target populations in schools-asymptomatic children-is unclear. To address this gap, we examined the positive and negative concordance between the BinaxNOW™ rapid SARS-CoV-2 antigen assay and an RT-PCR test among children at a community-based Covid-19 testing site. Methods We conducted rapid antigen (BinaxNOW™) and oral fluid RT-PCR (Curative Labs) tests on children presenting at a walk-up testing site in Los Angeles County from November 25, 2020 to December 9, 2020. Positive concordance was determined as the fraction of RT-PCR positive participants that were also antigen positive. Negative concordance was determined as the fraction of RT-PCR negative participants that were also antigen negative. Multivariate logistic regression models were used to examine the association between positive or negative concordance and participant age, race-ethnicity, sex at birth, symptoms and Ct values. Results 226 children tested positive on RT-PCR; 127 children or 56.2% (95% CI: 49.5% to 62.8%) of these also tested positive on the rapid antigen test. Positive concordance was higher among symptomatic children (64.4%; 95% CI: 53.4% to 74.4%) compared to asymptomatic children (51.1%; 95% CI: 42.5% to 59.7%). Positive concordance was negatively associated with Ct values and was 93.8% (95% CI: 69.8% to 99.8%) for children with Ct values less than or equal to 25. 548 children tested negative on RT-PCR; 539 or 98.4% (95% CI: 96.9% to 99.2%) of these also tested negative on the rapid antigen test. Negative concordance was higher among asymptomatic children. Conclusions Rapid antigen testing can successfully identify most COVID infections in children with viral load levels likely to be infectious. Serial rapid testing may help compensate for limited sensitivity in early infection.